2016
DOI: 10.2147/dddt.s97380
|View full text |Cite
|
Sign up to set email alerts
|

Papaverine inhibits lipopolysaccharide-induced microglial activation by suppressing NF-κB signaling pathway

Abstract: ObjectiveTo investigate the effects of papaverine (PAP) on lipopolysaccharide (LPS)-induced microglial activation and its possible mechanisms.Materials and methodsBV2 microglial cells were first pretreated with PAP (0, 0.4, 2, 10, and 50 μg/mL) and then received LPS stimulation. Transcription and production of proinflammatory factors (IL1β, TNFα, iNOS, and COX-2) were used to evaluate microglial activation. The transcriptional changes undergone by M1/M2a/M2b markers were used to evaluate phenotype transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Papaver spp. has various functional benefits that are widely used to treat various issues, such as dental problems [ 10 ], neuronal disorders [ 11 ], cough [ 12 ], pain relief [ 13 ], microbial infections [ 14 ], and cancer [ 15 ]. Some species’ seeds, pedicles, and petals are used in salads or sorbets [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Papaver spp. has various functional benefits that are widely used to treat various issues, such as dental problems [ 10 ], neuronal disorders [ 11 ], cough [ 12 ], pain relief [ 13 ], microbial infections [ 14 ], and cancer [ 15 ]. Some species’ seeds, pedicles, and petals are used in salads or sorbets [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammation with excessively activated microglia has been demonstrated to aggravate the pathophysiology of many neurodegenerative diseases, indicating the beneficial efficacy of microglia regulatory agents in the therapy of these disorders (23,24). As disclosed in our previous study, total astragalosides alleviated neuroinflammation via the inhibition of iNOS and other inflammatory cytokines in mice with experimental autoimmune encephalomyelitis (25).…”
Section: Discussionmentioning
confidence: 62%
“…A growing body of evidence suggests that inhibition of NF-κB can directly or indirectly promote neuroprotective M2 polarization of the microglia [31,32]. Dang et al [31].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…A growing body of evidence suggests that inhibition of NF-κB can directly or indirectly promote neuroprotective M2 polarization of the microglia [31,32]. Dang et al [31]. found that papaverine promoted the transformation of activated BV2 cells from M1/M2b to a neuroprotective M2a phenotype through NF-κB signaling pathway.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%